Genomic and epidemiological monitoring of yellow fever virus transmission potential - Faria, NR; Kraemer, MUG; Hill, SC; De Jesus, J; Aguiar, RS; Iani, FCM; Xavier, J; Quick, J; Du Plessis, L; Dellicour, S; Thézé, J; Carvalho, RDO; et al. (American Association for the Advancement of Science, 2018)
The yellow fever virus (YFV) epidemic in Brazil is the largest in decades. The recent discovery of YFV in Brazilian Aedes species mosquitos highlights a need to monitor the risk of reestablishment of urban YFV transmission in the Americas. We use a suite of epidemiological, spatial, and genomic approaches to characterize YFV transmission. We show that the age and sex distribution of human cases is characteristic of sylvatic transmission. Analysis of YFV cases combined with genomes generated locally reveals an early phase of sylvatic YFV transmission and spatial expansion toward previously YFV-free areas, followed by a rise in viral spillover to humans in late 2016. Our results establish a framework for monitoring YFV transmission in real time that will contribute to a global strategy to eliminate future YFV epidemics.